Hederasaponin C ameliorates chronic obstructive pulmonary disease pathogenesis by targeting TLR4 to inhibit NF-κB/MAPK signaling pathways - Yujie Ning; Liting Huang; Qin-Qin Wang; Lina Liu; Xinghua Ni; Xiaoyun Xie; Jingyu Liu; Qian Su; Shilin Yang; Renyikun Yuan; Hongwei Gao (Chinese Medicine)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a complex respiratory disorder characterized by persistent respiratory symptoms and progressive airflow limitation. Long-term exposure to harmful particulates and gases causes structural abnormalities in the airways and alveoli, activating NF-κB/MAPK signaling pathways that drive chronic inflammation and tissue remodeling. Key features include an imbalance between proteolytic enzymes and inhibitors mediated by matrix metalloproteinases, and excessive mucus secretion due to mucin overexpression. These factors exacerbate airway obstruction and inflammation, contributing to disease progression. Hederasaponin C (HSC), a triterpenoid saponin with anti-inflammatory properties, shows potential in mitigating COPD-related inflammation, but its precise mechanisms require further investigation. Methods We investigated the impact of HSC on COPD models induced by CSE + LPS using a comprehensive approach. In vitro studies included Western blotting, qRT-PCR, ELISA, and immunofluorescence to assess key proteins in NF-κB/MAPK signaling pathways, MMP9 and MMP12 expression, and mucin levels (MUC-5AC, MUC-5B). Binding affinity between HSC and TLR4 was evaluated using molecular docking, SPR analysis, and CETSA. DNA methylation at MUC-5B chr11:1243469 position was detected using an Agilent 2100 Bioanalyzer. In vivo, a COPD mouse model induced by cigarette smoke and LPS (CS + LPS) was developed, and HSC treatment effects were evaluated using H&E staining, multiplex immunofluorescence staining, Western blot, and ELISA kits. Results HSC significantly inhibited CSE + LPS-induced inflammation by targeting TLR4 and attenuating NF-κB/MAPK signaling pathways overactivation. It also downregulated MMP9, MMP12, MUC-5AC, and MUC-5B expression and suppressed MUC-5B chr11:1243469 position DNA methylation. In vivo, HSC alleviated COPD symptoms in CS + LPS-induced mice, reducing TLR4/NF-κB/MAPK signaling pathways overactivation and smoking-associated factors. Conclusion HSC targets TLR4, attenuates NF-κB/MAPK signaling pathways overactivation, reduces MMP9, MMP12, MUC-5AC, and MUC-5B expression, and suppresses MUC-5B chr11:1243469 position DNA methylation. These actions reduce inflammation, restore protease-antiprotease balance, and mitigate excessive mucus secretion, highlighting the promise of HSC as a viable treatment strategy for COPD management.